DESIGN AND DEVELOPMENT OF AN INTERNET OF THINGS (IOT) BASED REAL TIME MONITORING AND CONTROL SYSTEM FOR SMART INDOOR HYDROPONIC VERTICAL FARMING SYSTEM WITH ESP32 AND ADAFRUIT IO - Md Mahmud Yusuf; Shafrida Sahrani; Mohamad Hanif Md Saad; Mahidur Sarker; Muhd Zamry Abu Samah (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Vertical farming is an unconventional method of agriculture where crops are grown in a vertically stacked manner in a controlled environment either in indoor or outdoor setup. Hydroponic is a concept where crops are grown in water filled with mineral nutrients instead of soil. Hydroponic vertical farming system thus represents a farming fashion where crops are grown vertically, and their roots submerged in nutrient-rich water. In this paper, we have implemented a hydroponic vertical farming system and utilized the concept of Internet-of-Things (IoT) to monitor and control the environmental parameters in real time on a dashboard with ESP32, MQTT broker and Adafruit IO. The developed system acquires real-time environmental values such as temperature, humidity, nutrient concentration in water, level of water and nutrient supply, battery voltage, and power consumption. The challenges and future suggestions are also described in this paper.